Thermal Decomposition Kinetics of Poly(nButMA-b-St) Diblock Copolymer Synthesized by ATRP - Kurt, Adnan (Wiley, 2009)
The reaction mechanism of decomposition process and the kinetic parameters of the poly(n-butyl methacrylate-b-styrene), poly(nButMA-b-St), cliblock copolymer synthesized by atom transfer radical polymerization (ATRP) were investigated by thermogravimetric analysis (TGA) at different heating rates. TGA curves showed that the thermal decomposition occurred in one stage. The apparent activation energies of thermal decomposition for copolymer, as determined by the Kissinger's, Flynn-Wall-Ozawa and Tang methods, which does not require knowledge of the reaction mechanism (RM), were 112.52, 116.54, and 113.41 kJ/mol, respectively. The experimental results were compared with master plots, in the range of the Doyle approximation. Analysis of experimental results suggests that in the conversion range studied, 3-18%, the actual RM is an A(2) sigmoidal type. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 114: 624-629, 2009
Keywords: thermogravimetric analysis (TGA); activation energy; diblock copolymers; thermal properties